Samter's triad with aural involvement: a novel approach to management. Issue 12 (24th November 2014) - Sethukumar, P; Heywood, R; Narula, A
Abstract Background: Samter's triad is a well described condition manifesting as chronic rhinosinusitis with nasal polyposis, asthma and aspirin intolerance in a non-atopic individual. The underlying mechanism is still to be fully elucidated. However, aural disease has not been widely reported in these patients. In the few reported cases, most patients underwent major surgery with varying degrees of success. Case report: We report two Samter's triad patients with aural involvement. Both were successfully managed by conservative treatment, thus avoiding the need for major surgery. It appears that more Samter's triad patients may have aural disease than previously thought. Conclusion: We report good outcomes with conservative treatment, which is relevant because aural disease tends to reoccur in these patients.